2011
DOI: 10.1007/s12024-010-9215-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced post-mortem defect of the skull simulating an exit gunshot wound of the calvarium

Abstract: Case reportA severely burned body was found in a burnt-out apartment following a house fire. At the death scene, police investigators noted a defect at the back of the head of the deceased. This defect perforated the occipital bone and showed external bevelling. To clarify whether this skull wound corresponded to a gunshot exit wound and for identification purposes, a medico-legal autopsy was ordered.External examination of the body showed intense charring with skin burned away and musculature exposed, fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Heat-associated fractures have even been described in the skull, mimicking gunshot wounds. 17,18 However, postmortem radiographs and thorough examination of the bones and soft tissues can rule out projectile injury. Detectives in the current case proposed that the female decedent had sustained a gunshot wound to her head after seeing fractures of her skull.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-associated fractures have even been described in the skull, mimicking gunshot wounds. 17,18 However, postmortem radiographs and thorough examination of the bones and soft tissues can rule out projectile injury. Detectives in the current case proposed that the female decedent had sustained a gunshot wound to her head after seeing fractures of her skull.…”
Section: Discussionmentioning
confidence: 99%
“…However, when a forensic pathologist has to deal with charred remains, the task becomes tougher. In fact, the morphological features of burnt bones can become misleading: tissues are sub-jected to severe alterations and the clues they can provide can be extremely distorted (6)(7)(8)(9)(10). Recently, the issue of cremated remains had gained more attention in the forensic field, as well as injuries on burnt remains (6,(11)(12)(13)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…As bone becomes affected by many morphological changes, signs of trauma probably behave in the same manner. Furthermore, the effect of extreme heat or of the flames themselves may create misleading artifacts . Recent studies have demonstrated the survival of specific signs of trauma even when the tissues are exposed to high temperatures or to direct flames.…”
mentioning
confidence: 99%
“…Taphonomic inputs can further muddy the diagnostic waters by masking or mimicking gunshot trauma. For example, animal trophic activities may damage fracture margins [ 8 ], whilst exposure to fire may produce bevelled defects resembling conoidal wounds [ 9 , 10 ]. Differential diagnosis may be challenging in thinner cranial bones, such as the sphenoid, which do not exhibit bevelling [ 6 ].…”
Section: Introductionmentioning
confidence: 99%